Financial Resilience Strategy on Cancer Survivors Household in East Java - Maria Yovita R Pandin; Tries Ellia Sandari; Dedy Surahman; Achmad Daengs GS (Universitas Negeri Semarang, 2023)
The problem of this research is how to make a financial resilience strategy faced by households during the economic crisis. The purpose of this study is to analyze the strategy of household financial resilience during an economic crisis. The design in this study uses a quantitative approach by collecting data through surveys.Respondents in this study were breast cancer survivors in East Java.The findings in this study are that every household needs a financial strategy in dealing with a crisis.An adaptive capacity strategy is needed so that household financial resilience remains flexible.Absorption strategy is a strategy in building financial resilience capability which is always strived to be in a stable position.A transformative capacity strategy is carried out to build household financial resilience when experiencing financial shocks by making drastic changes to financial planning.